A Case of Lightning Stroke through the Cell-Phone - Keisham, Supriya; Sangma, Mitul M; Das, Nani Gopal; Ph , Memchoubi (Journal of Indian Academy of Forensic Medicine, 2015)
This is a case report of a man who was killed by a lightning stroke while using a cell-phone during a thunderstorm. The electric current in lightning is direct with a potential of 1000 million volts or more. A lightning bolt may injure or kill a person by a direct strike, a side-flash, or conduction through another object. In a direct strike or a side flash strike, the current can spread over the surface of a body, enter it or follow both routes. In a side flash strike, the flash of lightning hits an object e.g. a tree, and jumping from it, strikes the person. In conduction through another object, the lightning hits a metallic object, flows through it and strikes a grounded person touching it. In the present case, a flash of lightning hit the cell-phone in his hand and conducted the electric current through his body. On autopsy, a charred area was seen on his hand corresponding with the size of the cell-phone besides internal signs of asphyxia. This case report is done with the aim of spreading awareness and to take up precautionary measures while using cell-phone during a thunderstorm.